Tinjauan Kriminologi Terhadap Tindak Pidana Penadahan Barang Hasil Curian Kendaraan Bermotor di Kabupaten Karawang dihubungkan dengan Teori Perspektif Sosiologis (Studi Kasus di Polres Karawang) - Hanafi, IVAN; Guntara, Deny; Abas, Muhamad (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The rise in criminal acts involving stolen goods is a  massive problem for the community, especially in Karawang Regency. There are many cases of theft of motor vehicles and selling them to collectors. In this case, the collectors have quite an important role because the presence of the collectors opens the way for the perpetrators. motor vehicle theft. This research was conducted to find out the causes of crime in burglary cases and how to overcome this action. Therefore, criminology is very much needed for this research to find out what factors make a person commit the crime of stealing motor vehicles in Karawang Regency and what countermeasures are taken—by police officers to prevent such actions. The type of research used is empirical juridical and supported by secondary data conducted at the Karawang Police Station by conducting interview observations and other data collection related to the crime of holding goods stolen from motorized vehicles in Karawang Regency. Based on the results obtained in research on the criminal act of holding goods stolen from motorized vehicles in Karawang Regency, the author concludes that the factors that make a person commit a criminal act of holding are economic, educational, and work pressure factors that encourage him to commit a crime and the efforts of the police in dealing with this criminal act. is with Preventive and Repressive actions.